Mycotoxins in coffee: what reality? - Viegas, Susana (2017)
Coffee is a valuable product due to the still increasing demand for production and consume. Brazil, Vietnam and Columbia are the bigger producers and Finland, Norway and Netherlands are the countries with higher rates of consumption. Unfortunately, it is subjected to various contaminations that can have an important impact in consumer’s health and economy. The major compound of concern is ochratoxin A (OTA) but other mycotoxins can be present. However, roasting process has an important role in reducing mycotoxins presence, depending upon the combination of time and temperature. Since each European country applies different roasting conditions, significant differences in mycotoxins concentrations occur across the world even when the origin of the coffee beans is the same. Considering the above the aim of this study was to analyze mycotoxins (OTA, aflatoxins (AF) and citrinin (CIT)) in coffee ready to be consumed from different markets and different brands: Portugal (6), Austria (3), United States (2) and Timor (1). Twelve samples were collected from different types of brands sold as roasted beans. The extraction of OTA, CIT and AF was done on the immunoaffinity column Ochraprep (RBiopharm), CitriTest HPLC and AflaTest WB (Vicam), respectively. Mycotoxins were analyzed with HPLC-FLD (Merck-Hitachi). CIT and AF were not detected. OTA was detected in all the samples from Austria (2 results < 0.4 μg/Kg and 0.43 μg/Kg). In one of the Portuguese samples it was detected OTA (< 0.4 μg/Kg). Since the coffee beans have probably the same origin, it seems that indeed the roasting process adopted in each country and coffee industries influence the presence of mycotoxins. Further studies should be developed aiming to analyze other mycotoxins considering the possible climate changes influence. Additionally, a study should be developed to allow identifying how the roasting conditions adopted in each European country impact the presence of mycotoxins in coffee.